Bridging Micro and Macro Structures Through an Integrated Islamic Education Model for Strengthening Social Cohesion - Rizki, Muhammad; Mustanir, Mustanir; Silahuddin, Silahuddin; Jasafat, Jasafat; Sabirin, Sabirin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study examines the practice of integrated education in Aceh Besar, Indonesia, a region with strong Islamic traditions and the implementation of Islamic law, to explore how religious values are internalized while simultaneously fostering social cohesion and using a qualitative multiple case study design. This research was conducted at SMP Negeri 1 Darul Imarah, SMP Negeri 1 Ingin Jaya, SMP Negeri Ali Hasjmy (a boarding school), SMP Negeri 1 Darussalam, SMP Negeri 1 Kuta Baro, and SMP Negeri 3 Ingin Jaya. The method used was a qualitative approach, with data collected through in-depth interviews, focus group discussions, and document analysis. Data were analyzed thematically to identify patterns and mechanisms through which Islamic education translates into social practices. The findings reveal three interrelated mechanisms: (1) the internalization of Islamic values is promoted through curricula and activities that incorporate local wisdom, such as meuseuraya; (2) social cohesion is strengthened through structured collaboration between schools, families, and community institutions, enabling students to practice empathy, cooperation, and civic responsibility; and (3) normative Islamic teachings are connected to contemporary educational needs, including ethical engagement with modern social and digital contexts. These mechanisms function as a coherent educational ecosystem in which ethical development and community integration mutually reinforce one another. The study demonstrates that integrated education can operationalize universal Islamic principles within culturally relevant frameworks, translating moral values into practical social behaviors. While situated in Aceh Besar, the findings highlight processes by which Islamic education can bridge spiritual formation and social cohesion in contexts where religion and local culture intersect.